FORMATION AND DEVELOPMENT OF THE DIGITAL ECONOMY PROBLEMS AND RISKS - G.B. Yusupkhodjaeva (Scholar Express Journals, 2024)
The article analyzes the impact of the digital economy on the development of modern technology, innovative business models penetrate into all spheres of the economic life of society, influencing the economy, forming qualitative structural changes in it. The article provides an overview of the development of the digital economy in the world and Uzbekistan, identifies the risks and threats to the development of the digital economy, and suggests ways to overcome them. It has been established that today the electronic economy is already beyond the scope of purely economic processes. Digitalization is being introduced into social processes, the successful life of people increasingly depends on it, in addition, there is a large-scale introduction of digital technologies into the work of government organizations and structures. In this activity, it is necessary to take into account a number of problems, risks and threats identified in the article in order to focus resources and efforts on their neutralization.
Keywords: digital economy; threats and risks to sustainable development; economic growth; government regulation of the economy